An inter-ethnic study of gender differentiation and innovativeness among women entrepreneurs in Malaysia - A. Idris (South African Journal of Business Management, 2010)
Researchers have generally established the connection between innovativeness and cultural values. However, in these studies men are typically the majority of respondents. There is also no effort in these studies to treat women as a distinct cultural entity although there is evidence suggesting that social conditioning, particularly in masculine societies, induces gender-differentiated behaviors. This paper addresses these Issues via a quantitative study examining the effect of masculinity (Hofstede, 1980) on the innovativeness of Malay and Chinese women entrepreneurs in the Malaysian peninsula. Results strongly suggest that for women entrepreneurs, masculinity should not be treated as a single-construct dimension. Rather it should be split into two sub-constructs: ego orientation and gender differentiation. When the construct of masculinity is divided in this way, path analysis reveals that the Malay sample of women entrepreneurs is more innovative than the Chinese even though the latter has a higher index of ego orientation. This may be explained by the former's lower index of gender differentiation.
Keywords: 650